POLA REKRUTMEN PDIP, NASDEM DAN PSI DALAM PEMILIHAN CALEG DPRD DI KOTA DENPASAR - Sibagariang, Dede; Erawan, Ketut Putra; Ali Azhar, Muhammad (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT This study aims to determine the recruitment patterns of the three parties in the city of Denpasar who participated in the 2019 elections, namely PSI, PDIP and NasDem using the rational theory of Barbara Geddes: partisanship, meritocratic, survival and compartmentalization. The three parties also have differences in determining the recruitment of legislative candidates for the Denpasar City DPRD. This study uses qualitative methods with comparative characteristics, theory of Barbara Geddes, is that PDIP Recruitment is more directed towards partisanship, The NasDem Party leads to meritocratic, while PSI leads to survival, the goal is that cadres or legislative candidates from PSI are completely new or ways think it is not contaminated with the previous party. Keywords: political parties, recruitment, candidates